Assessment of statistical and empirical conversion methods of integration time for rainfall rate in Malaysia - Mohd Sobli, Nuurul Hudaa; Ismail, Ahmad Fadzil; Asnawi, Ani Liza; Wan Nordin, Mimi Aminah; Khairolanuar, Muhamad Haziq (Springer Verlag, 2016)
This paper presents some preliminary observations of assessments regarding the precipitation intensity conversion methods from 60- to 1-min integration time. There are two conversion methods were identified and used for this findings; Rice-Holmberg and Khairolanuar et al. conversion methods. Different type of precipitation were analyzed and implemented in analytical method of Rice-Holmberg and characteristics of rainfall rate distributions were evaluated from the empirical method of Khairolanuar et al. Rainfall intensity data were acquired from Malaysia Meteorological Department (MMD). The rainfall rate data consist of twelve consecutive months from January to December 2009. The evaluations for the acquired data were carried out to produce annual rainfall rate cumulative distribution and as well as its cumulative distribution at 1-min integration time utilizing the aforementioned conversion methods. The comparisons of the performance of these two methods were also examined. Based on the evaluation, it can be observed that Rice-Holmberg and Khairolanuar et al. produced percentage errors around 19% as compared to ITU-R P.837 at 0.01% of time exceedance.